'This is not right radicalism': Thomas Carlyle's dialogue with John Stuart Mill in The French revolution. (4th May 2021) - Malecka, Joanna
ABSTRACT: Thomas Carlyle's morally conservative mindset and post-Burkean imagery have rarely been linked to some of the most politically and artistically radical passages in The French Revolution: A History (1837), the general assumption being that it is Carlyle's rejection of the Presbyterian heritage that sponsors his most innovative social and political thought. This article argues that Carlyle's Scottish Calvinist perspective sponsors a radical cultural language at a time when his support for the French Revolution is scorned upon even in the professedly radical John Stuart Mill's Westminster Review . Carlyle draws from Mill's early fascination with the active role of the people in shaping the political reality and gives it a radical voice long after Mill had already lost his enthusiasm and adopted the Whig interpretation of the French Revolution as a necessary evil in the march of progress. In this context, Mill's early paean to Carlyle's French Revolution as a contemporary 'epic poem' is read as a doubtful compliment which obfuscates the more politically scandalous passages in Carlyle's oeuvre, such as Carlyle's deeply sympathetic depiction of the storming of the Bastille.